Gender Analysis in Verses of the Qur'an That Concern Trafficking - Muhammad Sofyan; Muhammad Shabrun Algifari; Eni Zulaiha (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of this study is to analyze the Islamic perspective on the practice of human slavery through verses from the Qur'an. This is done because human slavery and human trafficking are still widespread today. The method used in this study is literature analysis with a historical and phenomenological approach. The focus of this research covers modern slavery in the form of human trafficking, which is considered a determining factor in the existence of slavery in modern times. This research is also supported by data and strengthened by previous studies. The study concludes that initially the Qur'an acknowledged and accepted slavery because it was a reality that had existed for a long time. Therefore, it was impossible to eliminate it instantly and revolutionary, but in subsequent stages it was gradually reduced. This began with liberation from the practice through psychological, theological, and economic approaches, followed by the stage of physical liberation. Finally, it calls for the abolition and prevention of slavery. The Qur'an prohibits the practice of slavery in any form. The sources used were verses from the Qur'an, Hadith, and books of Tafsir, as well as national and international laws and regulations related to the prohibition of human trafficking.